Indigenous participation at international leveland disturbance to the state centrism in theinternational community (2015)
The article exposes the indigenous participation along the last decades, and its influence on the state centrism, which is the sustainer of the international law system. For this purpose we have studied analogies with other groups that have participated in the elaboration of international instruments. Thereafter we analyze the motivations of the participation of indigenous peoples and how this are related to indigenous sovereignty. We also expose the concepts in which indigenous participation and indigenous sovereignty are based on and their relation to international legal subjectivity. Before displaying the conclusions, the practical results of the research are presented in terms of institutionalism and how they could affect state centrism.